Phylogenetic relationships within the cahirinus-dimidiatus group of the genus Acomys (Rodentia: Muridae): new mitochondrial lineages from Sahara, Iran and the Arabian Peninsula - Frynta, Daniel; Palupčíková, Klára; Bellinvia, Erica; Benda, Petr; Skarlantová, Hana; Schwarzová, Lucie; Modrý, David (Zootaxa, 2010)
Spiny mice belonging to the cahirinus-dimidiatus group of the genus Acomys have become a widely used model in physiology and behaviour. To improve current knowledge concerning the phylogeny of this taxon, we analysed 24 samples from Libya, Chad, Egypt, Jordan, Cyprus, Crete, Turkey, Yemen and Iran. We sequenced the whole mitochondrial control region and part of the flanking tRNA genes for a total length of 986 to 996 bp and described 22 haplotypes. Our results confirmed that the Afro-Mediterranean and Asian clades are clearly distinct (p-distance = 6-8.1%). The former clade corresponds to A. cahirinus sensu lato (i.e. including also the Cretan A. minous, Cypriot A. nesiotes and Turkish A. cilicicus). Haplotypes of A. cahirinus from the E Sahara (S Egypt, SW Libya, N Chad) grouped with those of A. cilicicus and A. minous (p-distance ≤ 2.2%), while haplotypes of A. nesiotes grouped with one haplotype representing the commensal A. cahirinus from Cairo (p-distance = 1.2%). Close similarity among haplotypes from mainland Africa and NE Mediterranean (clade A. cahirinus sensu stricto) support the hypothesis that ancestors of A. nesiotes, A. cilicicus and A. minous dispersed most probably as commensal populations, thus questioning their status of valid species. The most surprising finding was the considerable genetic variation in Asia. In addition to a haplogroup from Sinai and Jordan (corresponding to A. dimidiatus sensu stricto), we detected two previously unknown haplogroups, from Yemen and Iran + United Arab Emirates. These clades are fairly distinct and separate species/subspecies status of these animals might be further considered.